Effect of Thermal Processing on Physicochemical and Antioxidant Properties of Raw and Cooked Moringa oleifera Lam. Pods - Abdur Razzak; Keya Rani Roy; Ummay Sadia; Wahidu Zzaman (International Journal of Food Science)
Moringa is regarded as a miracle tree because all components of the plant, including the roots, leaves, pod, and flowers, have significant nutritional and therapeutic value. Moringa oleifera Lam. pods have excellent antioxidant characteristics and are a good source of protein, carbohydrate, fat, vitamins, beta-carotene, amino acids, and phenolic compounds. The pods of Moringa oleifera Lam. were collected from the local market of Sunamganj, and their nutritional value was assessed in raw condition and after thermal processing. The goal of this research was to observe how the thermal temperature affected the antioxidant and physicochemical qualities of thermally-processed Moringa oleifera Lam. pods. Thermal treatment diminished the amount of crude protein, fat, carbohydrate, ash, ascorbic acid, and beta-carotene in the pods, as well as DPPH, total phenol content, and total flavonoid content. The moisture percentage of raw and thermally-processed Moringa oleifera Lam. pods was determined to be 83.12%, 86.03% with a total ash level of 2.01%, and 1.8%, respectively. The crude protein, fat content, and carbohydrate were 3.0%, 0.1%, and 3.2%, respectively, in thermally-processed pods. The values for total phenol content, total flavonoid content, vitamin C, DPPH free radical scavenging activity, and β-carotene were 28.13 mg, 2.98 mg, 38.23%, 3.98 mg, and 0.12 mg, respectively, in raw samples whereas 24.56 mg, 2.72 mg, 3.50 mg, 34.32%, and 0.0904 mg, respectively, in thermally-processed samples. According to the findings, Moringa oleifera Lam. pods have high nutritional content and thus can be used as an excellent source of diet, and even after thermal processing, a significant nutritive value remains in the Moringa oleifera Lam. pods.